Padrões de distribuição e endemismo da espécie Criticamente Ameaçada, Trichogenes claviger (Siluriformes, Trichomycteridae, Trichogeninae) - Silva, Juliana Paulo da (2023)
This study presents for the first time the use of environmental DNA (eDNA) for detection of an endangered fish species in Brazil. Trichogenes claviger occurs in first and second order forested streams only in the headwaters of the Itapemirim basin. Until then, the species was known only from two locations mountain regions, in the sub-basin of the Picada Comprida stream, a source of the Caxixe river. The study aimed to determine whether the eDNA metabarcoding approach works as an adequate tool to assess the presence of the species. Though, a 12S marker was created, specific for the T. claviger species. We found evidence of the catfish presence through eDNA samples in three of the ten sites sampled. In addition to the target species of this study, it was possible to collect traces of non-target species detected in the water samples. 25 species of vertebrates were identified, of which 15 were fish, 5 mammals and 5 birds. Among these records, we highlight the presence of exotic fish species, such as the tilapia Coptodon rendalli and Oreochromis niloticus, and the species of bird, Scytalopus speluncae, which is in Danger (EN) on the state list of Espírito Santo. Comparison between the methods for estimating species composition per sampled stream demonstrates that the eDNA metabarcoding approach identified more than twice as many stream species previously detected by traditional collection methods, which used fishing gear such as nets and sieves. The results achieved ensure a better understanding of the spatial distribution dynamics of T. claviger, its conservation status, as well as insights into the vertebrate community associated with catfish environments.